2018
DOI: 10.21071/az.v67i259.3801
|View full text |Cite
|
Sign up to set email alerts
|

Endogamia em um rebanho de caprinos da raça Anglo Nubiana

Abstract: O objetivo desta pesquisa foi descrever a estrutura da população e avaliar os efeitos da endogamia sobre peso corporal em diferentes idades em caprinos Anglo Nubiana. Foram utilizados dados de pedigree de 1.104 animais nascidos de 1980 a 2010. O programa Endog foi utilizado para analise do pedigree e estimação dos parâmetros populacionais. O efeito da endogamia foi verificado pelo teste t, avaliando contraste por meio de uma sub-rotina do aplicativo MTDFREML. Do total de animais estudados, 85,96% apresentaram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Most studies have shown that inbreeding has no significant effect on fleece traits ( 36 ). Sousa et al ( 44 ) reported that inbreeding had a significant effect on the body weight of Anglo Nubiana breed goats. Vostra-Vydrova et al ( 37 ) indicated that inbreeding coefficients showed a significant negative influence on milk performance in the White Shorthair goat breed.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown that inbreeding has no significant effect on fleece traits ( 36 ). Sousa et al ( 44 ) reported that inbreeding had a significant effect on the body weight of Anglo Nubiana breed goats. Vostra-Vydrova et al ( 37 ) indicated that inbreeding coefficients showed a significant negative influence on milk performance in the White Shorthair goat breed.…”
Section: Discussionmentioning
confidence: 99%